Irrational beliefs and their relation to the level of academic ambition for secondary third-year students. - laagug, khadija; rakza, samira (Journal of Social Sciences and Humanities, 2021)
This study aimed to find out the extent of the spread of Irrational beliefs among third secondary students and their relation to the level of academic ambition, In addition to knowing whether there are statistically significant differences between the sexes in both variables. To achieve the objectives of the study, we used The test of Irrational beliefs of Dr. Sulaiman Al-Rihani (1987), the test of academec ambition level of Mohammad Boufatah (2005, and after ascertaining their psychometric characteristics, They were applied to a sample of 120 pupils. The results indicated the spread of Irrational beliefs among third-year high school students, in addition to the lack of a correlation between Irrational beliefs and the level of academic ambition among third year primary students, and the existence of statistically significant differences between the sexes in Irrational beliefs in favor of Females in three ideas: the course of things contrary to what the individual wishes, impulsive recklessness, disaster prediction, lack of statistically significant differences between the sexes in the level of academic ambition .